Careers without Gender: Strategies to Promote Gender Equality in Engineering - Santos, Bertha (2020)
In the last years, European Union has strongly promoted to increase the number of women in STEM (Science, Technology, Engineering and Maths) courses at universities, and consequently women presence in these labour markets. This effort is clearly reflected in the “Strategic engagement for gender equality 2016-2019” of the European Union, in the key action “promoting gender equality in all levels and types of education, including in relation to gendered study subject choices and careers” as a way to reduce the gender pay, earnings and pension gaps and to fight poverty among women, which are important concerns in several European countries. University of Beira Interior (UBI) has a gender equality plan (GEP) since 2011 and recently become a partner of the project “Women engineers for a day” (in Portuguese "Engenheiras por um dia"), developed under the “Agenda for equality in the labour market and in enterprises”, framed in the “National strategy for equality and non-discrimination 2018-2030”. The main objectives of the project are to promote engineering programs and to share experiences of women engineering professionals and university students with the students of secondary schools. This paper aims to report and discuss some of the strategies adopted by the departments of Civil Engineering and Electromechanical Engineering of UBI in the promotion of engineering programs in secondary schools, as well as some approaches carried out in university classes to ensure gender neutrality and gender balance. The experience of the two departments shows that secondary school students are unfamiliar with most aspects of the engineering occupations as well as women potentialities in this field of knowledge. The contact with successful women storytelling in engineering; sharing sessions of real-world experiences of women engineers and practical hands-on and ICT activities have demonstrated to be efficient approaches. Still, many obstacles remain, for example, most of the university classroom materials (image, language, real world examples, etc.) do not promote gender equality in the engineering education.